2007
DOI: 10.1080/00365540601137379
|View full text |Cite
|
Sign up to set email alerts
|

Acute demyelinizating encephalomyelitis (ADEM) as initial presentation of primary HIV infection

Abstract: The authors report a patient with sexual exposure, clinical symptoms, MRI, virological and CSF findings suggestive of acute demyelinizating encephalomyelitis (ADEM) as initial presentation of primary HIV infection. The aetiology, pathophysiology, diagnosis, and treatment of ADEM is reviewed, and the sparse existing literature on ADEM and HIV infection is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Neither CD8 ϩ naïve nor central memory cells were related to NAA [23][24][25] A handful of case studies during PHI have described profound neurologic changes that can occur with HIV seroconversion including transient encephalopathy, frank meningoencephalitis, and demyelinating disease. 20,21,25 However, it is generally believed this early infection in non-rapid disease animals and humans is typically transient and productive infection is not thought to occur again until the development of AIDS. 24,26 The early HIV subjects were enrolled in this study within months of their seroconversion, during an early stage of infection, and did not report severe neurologic problems or have significant structural changes observed by MRI.…”
Section: Correlations Of 1 H Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Neither CD8 ϩ naïve nor central memory cells were related to NAA [23][24][25] A handful of case studies during PHI have described profound neurologic changes that can occur with HIV seroconversion including transient encephalopathy, frank meningoencephalitis, and demyelinating disease. 20,21,25 However, it is generally believed this early infection in non-rapid disease animals and humans is typically transient and productive infection is not thought to occur again until the development of AIDS. 24,26 The early HIV subjects were enrolled in this study within months of their seroconversion, during an early stage of infection, and did not report severe neurologic problems or have significant structural changes observed by MRI.…”
Section: Correlations Of 1 H Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…10,11 Little is known about the brain during PHI and all early HIV-infected individuals were recruited based on the presentation of symptoms of acute viral ailment and not the occurrence of neurologic deficits, although studies have suggested the presence of brain abnormalities during this time. [20][21][22] Previous magnetic resonance studies have indicated that the frontal cortex shows signs of damage and dysfunction during the asymptomatic stage of infection, long before onset of AIDS or related dementia. Significant reductions in NAA/Cr were observed in the frontal gray matter tissue of relatively healthy, cognitively asymptomatic (or even with ADC score 0.5), chronically HIV-infected subjects.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…have reported a 45-year-old bisexual male with clinical symptoms (cognitive dysfunction and right hemiparesis), MRI, and CSF examination findings suggestive of acute demyelinating encephalomyelitis as the initial presentation of primary HIV-infection. [10] Allen et al . had reported a 32-year-old homosexual male presenting with behavioral changes and diagnosed as acute demyelinating encephalomyelitis with a 5 year-old history of HIV-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Of almost 4,000 papers considered, we selected 13 articles respecting criteria of acute onset, unknown aetiology and disagreement with diagnostic criteria for MS (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In one paper, published in 1985 (16), the virus responsible for the immunodeficiency is named HTLV-III instead of HIV, but it is known that the two definitions corresponded at that time.…”
Section: Resultsmentioning
confidence: 99%